OSCAR WILDE’S CAMOUFLAGE CONFESSION AS SEEN IN THE STAR CHILD, AND THE SELFISH GIANT FAIRY TALES - Widiyanti, Ana (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2021)
Abstract The studies on Oscar Wilde’s fairy tales are mostly concern to reveal their moral values since fairy tales are usually written for children. Some researchers consider that fairy tales with their imaginative languages carry only a narrow or simple message to educate children with the result that make some of them reluctant to put it seriously as an object of research. Rather, this library research concern to reveal Oscar Wilde’s world view and the hidden message lied behind the symbolic language meaning in both The Start Child and The Selfish Giant Fairy tales. This research applies the semiotic and genetic structuralism approach. In analyzing the data, the researcher uses the descriptive qualitative method. The result of the study shows that both Oscar Wilde The Star Child and The Selfish Giants carry more than just moral values suitable for children, but some deep lessons for adults. Both of the fairy tales convey Wilde's camouflage confession of life in which he regrated his bad action and his losing hope condition when he has to experience bankruptcy and lived in prison. The result of the study also shows that both the fairy tales present important moral value, that is to show the readers the importance of sharing, caring, respect, and self-evaluation to be a better individual and to live life to the fullest. Keywords: fairy tales, genetic structuralism, symbolic language. Abstrak Penilitian terhadap fairy tales karya Oscar Wilde kebanyakan ditujukan untuk mengungkap nilai-nilai moral yang ada didalamnya saja. Hal ini dikarenakan fairy tales pada dasarnya ditulis untuk anak-anak. Kebanyakan para peneliti mengganggap fairy tales hanya mengandung nilai-nalai moral yang sangat sederhana sehingga sehingga banyak peneliti yang merasa enggan untuk menjadikannya bahan kajian yang serius. Berbeda dengan penelitian lain, penelitian Pustaka ini difokuskan untuk mengungkap pandangan dunia Oscar Wilde dan pesan moral yang sebenarnya ingin disampaikan melalui Bahasa-bahasa simbolik yang digunakan. Penelitian ini menggunakan pendekatan semiotic dan genetic strukturalisme, sedangkan dalam menganalisis data, peneliti menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa dua fairy tales The Star Child dan The Selfish Giant tidak hanya sekedar mengandung pesan yang cocok untuk anak-anak, akan tetapi juga mengandung pelajaran yang dalam untuk orang dewasa. Kedua fairy tales tersebut menyampaikan kamuflase pengakuan diri Wilde karena Tindakan buruknya dalam hidup dan kehilangan harapannya Ketika ia mengalami kebangkrutan dan hidup dalam penjara. Hasil penelitian juga menunjukkan pelajaran moral pada pembaca tentang pentingnya berbagi, berempati, menghormati, dan mengevaluasi diri untuk menjadi individu yang lebih baik. Keywords: fairy tales, genetic structuralism, symbol language.